Speaking and thinking in Latin: some dead languages are alive and thriving in some very modern disorders - Jane Whittaker (BJPsych Bulletin)
As psychiatrists, we are hopefully especially attuned to the power of language, especially the words we use when discussing sensations, thoughts and bodies. This article explores some of the heritage of medical language of today, drawing on classical Latin and how this interfaces with our day-to-day practice, with special reference to eating disorders.